Penerapan Metode Pekerja Sosial Case Work dalam Peningkatan Kemampuan Bahasa Inggris Anak di Panti Asuhan Ora Et Labora Nusantara Medan - Ramadani, Putri; Pirandy, Gusti (Yayasan Daarul Huda Kruengmane, 2025)
In today's era of globalization, English is one of the most important things to learn. English serves as the key to accessing wider educational and career opportunities, as well as a tool for international communication, information, science and technology. English language skills are essential for all members of society. This is also felt by young people who are learning. The constraints on English language learning can be more significant for children of Social Welfare Service Recipients (PPKS), especially for those living in orphanages. the purpose of this study is the application of the case work method in an effort to improve children's English language skills at the Ora et Labora Nusantara Medan Orphanage. This research is expected to provide an overview of how effective the case work approach is and offer practical suggestions for orphanages and education and social work practitioners in dealing with similar cases.